STYRNING AV ROBOT MED HJÄRNVÅGOR. En förstudie av gränssnitt med öppen källkod - Källander, Sara; Johansson, Martin (My University, 2018)
This report investigates possibilities and difficulties with the OpenBCI Ganglion equipment that allows for monitoring of brain activity through EEG (Electroencephalography) for non professionals. This type of technology has previously been exclusive for researchers and medical professionals and it is therefore interesting to explore new user scenarios such as controlling external devices through BCI (Brain Computer Interface). Due to limitations it is mainly the alpha waves that are examined as they have a large amplitude and are the only type of brain wave that appear to provide a satisfactory signal with regard to both control of brain activity and amplitude of the signal. Two open source pieces of software are used to manage the hardware and signal processing, OpenBCI GUI and BrainBay. Attempts are made to connect the EEG system with an external device, a Sphero robot. However, problems with the software prevented this from being completed. The conclusion is that it is possible to control external devices with brain activity using this equipment, however, only using one channel and with significant delay. The limitations in both hardware and software, and in the ability to consciously influence the brain’s activity make the system dfficult to apply in situations where high reliability or precision is required. The report is written in Swedish.
Keywords: Elektroteknik och elektronik; Electrical Engineering, Electronic Engineering, Information Engineering